A carbon and nitrogen isotopic investigation of a case of probable infantile scurvy (6th–4th centuries BC, Slovenia). (April 2020) - Nicholls, Rebecca; Buckberry, Jo; Beaumont, Julia; Črešnar, Matija; Mason, Phil; Armit, Ian; Koon, Hannah
Highlights: Combined osteological and high resolution isotope data has been used to interpret an individual's life history. The infant presented skeletal lesions consistent with chronic malnutrition, probably scurvy. High δ 13 C and δ 15 N values that do not support a simple dietary interpretation. Isotopic data is complex and should not be interpreted in isolation. Abstract: This paper presents a case study of a young infant, from a larger isotopic and osteological investigation of Bronze/Iron Age (14th-4th century BCE) skeletal assemblages from Croatia and Slovenia. The osteological analysis of this infant identified pathological lesions including abnormal porosity and new bone formation consistent with malnutrition and phases of recovery. The distribution and appearance of these pathological lesions (i.e. diffuse micro-porosities and plaques of subperiosteal new bone formation on the skull and long bones) led to the conclusion that this infant probably suffered from scurvy (vitamin C deficiency). The diet and nitrogen balance of this individual were investigated by incremental dentine sampling and stable carbon and nitrogen isotope analysis. This sampling method provided a high resolution record of dietary and metabolic changes from pre-birth to around the time of death. The resulting isotope data exhibited unusually high δ 13 C values for this region and time period (between −11.3‰ and −12.6‰), while δ 15 N values were observed to be c. 3‰ above that of rib collagen sampled from contemporary adults recovered from the same site. The isotope profiles generated from the incremental dentine analysis show that δ 13 C and especially δ 15 N continue to increase until death. The evidence from the skeletal remains and high resolution isotopic data support the hypothesis that this infant suffered from severe malnutrition and an increasingly negative nitrogen balance. The paper discusses some scenarios which could have resulted in these unusual isotope ratios, whilst considering the diagnosis of possible metabolic disease. The paper also addresses the need for context when interpreting isotopic results. The isotope data should not be viewed in isolation, but rather as part of a multidisciplinary approach, considering the multiple causes of isotopic variability.